1988
DOI: 10.1111/j.1349-7006.1988.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Acquired Resistance to Cisplatin by a Human Ovarian Cancer Cell Line

Abstract: The present study was designed to elucidate the mechanism of resistance to cisplatin. A cisplatin‐resistant cell line (KFr) was established from KF cells derived from human serous cystadenocarcinoma of the ovary. The DNA histogram revealed an increase of S‐phase cells and a decrease of G1‐phase cells in cultured KFr cells, compared to that in cultured KF cells. Although the cisplatin content in the KF cells incubated with cisplatin at 10 μg/ml increased in a time‐dependent manner, that in the KFr cells remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…For this purpose, we used CDDPresistant ovarian cancer cell line, KFr13 cells, established from KF28 cells derived from human serous cystadenocarcinoma of the ovary. 23 The IC50 of CDDP was compared among KF28, KFr13 and SKOV3 cells and is shown in Figure 3a. KFr13 cells exhibited much higher IC50 than KF28 or SKOV3 cells, as expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we used CDDPresistant ovarian cancer cell line, KFr13 cells, established from KF28 cells derived from human serous cystadenocarcinoma of the ovary. 23 The IC50 of CDDP was compared among KF28, KFr13 and SKOV3 cells and is shown in Figure 3a. KFr13 cells exhibited much higher IC50 than KF28 or SKOV3 cells, as expected.…”
Section: Resultsmentioning
confidence: 99%
“…KF28 cells were derived from serous cystadenocarcinoma of the ovary, from which CDDP-resistant KFr13 cells were established. 23 Both cells were cultured in the above conditions.…”
Section: Cell Culturementioning
confidence: 99%
“…Cell Culture-Human ovarian cancer cell line HRA was grown and cultured as described previously (16). The HRA cells were maintained in RPMI 1640 medium supplemented with 10% FBS in a cell culture incubator (constantly set at 37°C with 5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Teicher et al (1986) reported that a CDDPresistant head and neck squamous cell carcinoma cell line (SCC-25/CP) showed cross-resistance to methotrexate, but not to FUra. In addition, Kikuchi et al (1988) reported that a CDDP-resistant cell line, KFr, derived from human serous cystadenocarcinoma of the ovary, showed no cross-resistance to FUra. Accordingly, the determinants relating to the sensitivity or resistance to FUra in CDDP-resistant cell lines might differ with the cell line.…”
mentioning
confidence: 99%